PENGARUH LABA KOTOR, LABA OPERASI, DAN LABA BERSIH TERHADAP PREDIKSI ARUS KAS DI MASA MENDATANG (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2020) - M. Jauhar Robani; Anik Malikah; Afifudin Afifudin (Universitas Islam Malang, 2022)
This research was conducted with the aim of knowing the effect of gross profit, operating profit and net profit on the prediction of future cash flows either simultaneously or partially. manufacturing companies listed on the Indonesia Stock Exchange. The data source can be obtained from the Indonesia Stock Exchange website namely www.idx.co.id. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The sampling method in this study was using purposive sampling method with a total sample of 47 manufacturing companies. The results showed that simultaneously gross profit, operating profit and net profit simultaneously had a significant effect on predicting future cash flows with an F test value of 84.981 and a significance value of 0.000. Partially, a). Gross profit is influential in predicting future cash flows with the value of Sig. 0.000 < 0.05. b). Operating profit has an effect on predicting future cash flows with the value of Sig. 0.000 < 0.05. c). Net income is influential in predicting future cash flows with the value of Sig. 0.000< 0.05.Keywords: gross profit, operating profit, net profit and cash flow.